Quantitative Determination of Ethyl Glucuronide and Ethyl Sulfate in Postmortem and Antemortem Whole Blood Using Phospholipid Removal 96-Well Plate and UHPLC–MS-MS. Issue 4 (20th August 2020) - Sidqey, Delvin; Liane, Veronica Horpestad; Kristoffersen, Lena
Abstract: Postmortem ethanol formation is a well-known problem in forensic toxicology. Ethyl glucuronide (EtG) and ethyl sulfate (EtS) are ethanol metabolites that can be used to distinguish antemortem alcohol intake from postmortem formation of ethanol and in addition can be a helpful tool in assessment of the hip-flask defense. To an aliquot of 100 µL whole blood, internal standard (IS) and water was added before protein precipitation treatment (PPT) with ice-cold acetonitrile (ACN). The supernatants were filtered through a 96-well phospholipid removal plate, evaporated to dryness and reconstituted in 150 µL water/ACN/formic acid (FA). Identification of compounds was performed using multiple reaction monitoring (MRM) in negative mode. Gradient elution was performed on a C18 column with methanol (MeOH) and 0.1% FA. The run time was 4.5 min, and 0.5 µL was injected on an ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS-MS) instrument. Linearity was achieved (coefficient of determination (R 2 ) ≥ 0.999) for EtG in the range of 0.089 to 22 mg/L (0.40–100 µM) and EtS 0.025 to 6.3 mg/L (0.20–50 µM). The limit of quantification (LOQ) was 0.067 mg/L (0.30 µM) for EtG and 0.019 mg/L (0.15 µM) for EtS. Between assay accuracy was –15% to 8% and precision reported as relative standard deviation (RSD) was ≤ 4.5%. Precision, estimated as the RSD of the concentration difference between results from two independent analyses of authentic whole blood samples, was ≤ 6.7%. Recovery was ≥ 61% for EtG and ≥ 77% for EtS and matrix effects (ME) were 99% to 103%. Method comparison was carried out with a previously used UHPLC–MS-MS method, and satisfactory agreement was achieved, and external proficiency testing control samples had z-score < ± 1. The method has been used in routine work for more than 4 years analyzing about 6, 000 antemortem and postmortem whole blood samples and has proven to be robust and reliable.